Diagnosis and Management of Immunotherapy-related Liver Toxicity - HUA Yuwei (Editorial Office of Medical Journal of Peking Union Medical College Hospital, 2021)
Immune checkpoint inhibitors have revolutionized the treatment of cancer. With the increasing use of immunotherapy, clinicians have observed that immunotherapy is often related to a spectrum of adverse events. Liver toxicity is one of the most common and severe immune-related adverse events. It is very important to increase awareness and outline a clear and detailed strategy of managing immune-related liver toxicity. Some guidelines have published systematic advice on the management of immune-related liver toxicity. However, there are controversial problems remaining, including the levels of liver toxicity, the minimal effective dosage of hormone, treatments for hormone-refractory patients, and immunotherapy re-challenge. Additional, finding predictors with high specificity and sensitivity is a pressing concern.